Study about Evolution and Controlling of the Plykin - Newhouse Attractor by the Pyragas Method - Belyakin, Sergey; Shuteev, Sergey; Kyznetsov, Sergey (New Trends in Physical Science Research Vol. 1, 2022)
In the present contribution consideration is being given to an autonomous physical system which is characterized by the presence of the attractor of a hyperbolic type. We study the possibility of controlling and stabilizing the Plykin-Newhose attractor of this type by the Pyragas method. The choice of the method of control. As such it is possible to use an external signal or the introduction of additional delayed feedback. (Both methods can be realized primarily during the schematic simulation, then in a real experiment). It might also be interesting to think about the realization of a more complicated scheme of control of the type suggested in the work for the stabilization of unstable periodic orbits belonging to the attractor.